Succession process and the efficacy of firms: the case of family firms - Silveira, Juvêncio Manuel Mouco da (2013)
This study investigates the complexity and the evolution of the succession process and its impact on the performance of the family businesses in Portugal, as the succession process may dictate the continuance or closure of the family business. It is true that most businesses in today´s World do reveal a familial dimension; therefore these businesses contribute to the wealth and the generation of employment through their leadership and entrepreneurial initiatives in every country in the Globe. The empirical analysis on the effects of the transmission on the efficacy of the family businesses as well as the effects of the socio-emotional wealth is conducted through a random sample of family businesses. Empirical research is conducted through the mixed methods approach. The present financial and economic environment in Portugal and in Europe has to be considered when analyzing the results. It is outstanding the performance of the analyzed family businesses, as the Portuguese family businesses face the growing global competitive environment, as these businesses also face their internal turmoil, affecting not only the family business, but all those directly and indirectly involved. In the context of this study, it is vital that the competence and aptitude of the next generation is such as to generate within the respective business environment through their developed entrepreneurship, the required results leading to the positive performance to attain the predetermined goals, fundamental for the continuance of the family legacy, such as the financial performance in order to guarantee the family socio-emotional wealth in the future. It is fundamental for the family business to remain competitive, profitable and a basis for the family socio-emotional wealth long after the transmission process onto the new generation is concluded, achievable only through the competence and entrepreneurial capability of the new generation.